Case Report : Solusio Plasenta Pada Kehamilan Preterm Yang Terdiagnosa Plasenta Previa Sebelum Tindakan Sectio Caesarea - Mofri Lindo (LPPM Universitas Abdurrab, 2024)
The maternal mortality rate in Indonesia is still high. According to the Indonesian Household Health Survey (SKRT) in 2001 found that bleeding in pregnancy contributes as the main cause of maternal mortality. Antepartum hemorrhage can be caused by placental abruption (PA) and placenta previa. This bleeding condition is an emergency case because it threatens the lives of both mother and fetus (mother-fetal dyad). Placental abruption is usually accompanied by pain due to continuous uterine contractions. In this case, although concealed hematoma exists in almost 80% of PA cases, the mother shows no sign or symptom even though the fetus is severely at risk. This condition can cause delayed management that leads to mother and fetal mortality, known as asymptomatic placental abruption.